Clarification of morphology and distribution of Thalictrum fortunei (Ranunculaceae) from China, with reduction of T. fortunei var. bulbiliferum to its synonymy - Zeng, You-Pai; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2022)
Critical observations on herbarium specimens and studies of living plants in the wild and in cultivation demonstrate that plants of Thalictrum fortunei with bulbils borne in leaf axils do not deserve recognition as an independent variety, i.e. T. fortunei var. bulbiliferum, with bulbils frequently occurring in late flowering and fruiting plants of this species. We therefore reduce T. fortunei var. bulbiliferum to the synonymy of T. fortunei. The description of hairiness is added for this species, which has been previously described as glabrous throughout. Morphological and geographical confusion involving T. fargesii and T. fortunei is also clarified.